2017
DOI: 10.1177/0033294117713495
|View full text |Cite
|
Sign up to set email alerts
|

Self-Concealment Mediates the Relationship Between Perfectionism and Attitudes Toward Seeking Psychological Help Among Adolescents

Abstract: One of the biggest barriers in treating adolescents with mental health problems is their refusing to seek psychological help. This study was designed to examine the relationships between two forms of perfectionism, self-concealment and attitudes toward seeking psychological help and to test the mediating role of self-concealment in the relationship between perfectionism and attitudes toward seeking psychological help among Malaysian high school students. The participants were 475 Malaysian high school students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Many students experiencing psychological problem but felt hesitant to seek help from professional mental health care (Abdollahi, Hosseinian, Beh-Pajooh, & Carlbring, 2017). Person who experiences psychological health problems ideally received access to getting assistance from professional staff or with fully aware themselves seeking and seeing the counselors, psychologists or people who are competent on the field of psychological health.…”
Section: Introductionmentioning
confidence: 99%
“…Many students experiencing psychological problem but felt hesitant to seek help from professional mental health care (Abdollahi, Hosseinian, Beh-Pajooh, & Carlbring, 2017). Person who experiences psychological health problems ideally received access to getting assistance from professional staff or with fully aware themselves seeking and seeing the counselors, psychologists or people who are competent on the field of psychological health.…”
Section: Introductionmentioning
confidence: 99%
“…With these studies as a backdrop, there are several reasons why self-help might be especially useful for perfectionism and in the context of soccer. In regards to perfectionism, self-help books may be especially useful for managing perfectionism as perfectionism is related to lower likelihood of seeking help (e.g., Ey et al, 2000) and related to more negative attitudes towards help-seeking in other contexts (e.g., Abdollahi et al, 2017). This reflects an apparent reluctance to reveal imperfections to others and project an image of perfection to others at all times (Hewitt et al, 2004).…”
Section: Interventions Inside and Outside Of Sportmentioning
confidence: 99%
“…Research on perfectionism and subjective well‐being (Mackinnon & Sherry, 2012) found perfectionistic self‐presentation to mediate the relationships between perfectionistic concerns—including socially prescribed perfectionism—and subjective well‐being (Mackinnon & Sherry, 2012). Also, the before‐mentioned study on perfectionism, self‐concealment, and positive attitudes towards help‐seeking suggested that perfectionistic self‐presentation mediated the relationships between dispositional perfectionism and help‐seeking attitudes (Abdollahi et al, 2017). Consequently, it was conceivable that perfectionistic self‐presentation would also mediate the relationships between dispositional perfectionism, self‐stigma, and coping.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study (Abdollahi, Hosseinian, Beh‐Pajooh, & Carlbring, 2017) examined dispositional perfectionism, self‐concealment, and positive attitudes towards seeking psychological help in high school students which is relevant in the present context because perfectionistic self‐presentation is intimately related to self‐concealment (D'Agata & Holden, 2018) and self‐stigma of seeking help is inversely related to positive attitudes towards seeking help (Vogel et al, 2006). As expected, both socially prescribed perfectionism and self‐concealment showed significant negative relationships with positive attitudes towards seeking help, but self‐oriented perfectionism showed a significant positive relationship indicating that self‐oriented perfectionism may not be as problematic for help‐seeking as socially prescribed perfectionism and perfectionistic self‐presentation.…”
Section: Introductionmentioning
confidence: 99%